An evaluation of 113mindium DTPA chelate in the measurement of gastric emptying by scintiscanning. Issue 8 (August 1971) - Heading, R. C.; Tothill, P.; Laidlaw, A. J.; Shearman, D. J. C.
Abstract : The sequential scintiscanning technique was used to determine gastric emptying rates in adult human subjects after ingestion of a meal of cornflakes and milk to which a gamma-emitting radioactive isotope had been added. Comparison of emptying rates using 113m In DTPA chelate and 51 Cr sodium chromate showed that significantly slower rates were recorded with chromate, and studies in vitro demonstrated adsorption of chromate to the solid component of the meal. The results imply that the liquid phase of the gastric contents after a meal is discharged through the pylorus more rapidly than the solid phase. Scintiscanning with indium chelate provides a measurement of the emptying of the liquid phase of the gastric contents.